Effect of the Use of Birth Balls on the Reduction of Pain and Duration of Labor During the First Stage of Active and Second Stage of Labor in Primigravida Maternity - Rahmi Mutia Ulfa (Science Midwifery, 2021)
Labor pain is caused by contracting the uterine muscles pushing the fetus out. Labor mothers find it difficult to adapt to the pain of labor, especially primigravidas, this can cause prolongation of the first stage of labor. There are two ways to reduce labor pain, namely pharmacology and non-pharmacology. One of the non-pharmacological methods is the use of a birth ball. The purpose of this study was to assess the effect of using a birth ball on the reduction of pain during the first stage of active phase and duration of stage I and duration of stage II of labor. This study used an experimental design with a pretest-posttest control group design. The sample consisted of 13 treatment people and 13 controls with the Consecutive Sampling technique. The pain scale was measured by the Faces Pain Rating Scale and the duration of the active phase I and the second stage of labor using a partograph. The difference in pain scores and duration of stage I and duration of II for the treatment and control groups were tested with T-independents if the data were normally distributed and the Mann-Whitney test if the distribution was not normal. There was a difference in the effect of using a birth ball on the reduction of pain in the first stage of the active phase in primigravida with p value = 0,000 and there was also a difference in the effect of using a birth ball on the duration of labor during the active phase in the treatment and control groups with p = 0,000, while for the duration of labor. during the second stage of labor, there was no difference in the effect of using a birth ball with p = 0.160. The use of birth balls is proven to reduce labor pain during the active phase and accelerate the duration of the I stage. Birth balls are recommended to be used as an alternative to reducing labor pain in midwifery services.